Southwest Airlines and American Airlines: aligning operations with strategy - Van Mieghem, Jan A. (Henry Stewart Talks, 2017)
This case study describes the ways in which Southwest Airlines and American Airlines implement dramatically different operations strategies to support their contrasting competitive strategies.